INOVASI MODEL PEMBELAJARAN AKTIF DALAM PJOK: SENAM IRAMA, PERMAINAN EDUKATIF, DAN PBL DI SMK NEGERI 8 PALEMBANG - Fitriyani; Putri Imelda; Ahmad Syarif Maliki; Yogi Pratama; Lusiana (PT. Hasba Edukasi Mandiri, 2026)
Active learning in Physical Education, Sports, and Health (PJOK) is important because students need learning experiences that involve movement, interaction, cooperation, and reflection. In vocational schools, PJOK should not only train physical skills, but also support discipline, confidence, teamwork, sportsmanship, and healthy living habits. This article aims to describe the innovation of active learning models in PJOK through rhythmic gymnastics, educational games, and Problem Based Learning (PBL) at SMK Negeri 8 Palembang. This article used a descriptive qualitative approach because the focus was to describe the learning process, student engagement, responses, obstacles, and learning solutions, not to measure statistical effects. Data were collected through observation of PJOK activities in the school field and classroom, field notes during teaching practice, informal question-and-answer activities with teachers and students, and photo documentation. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings show that active learning can make students more involved in PJOK activities. Rhythmic gymnastics encouraged students to follow instructions, coordinate movements, maintain body rhythm, and build group compactness. Educational games created a more lively, enjoyable, and cooperative learning atmosphere through simple equipment such as cones, balls, and field lines. PBL encouraged students to understand movement problems, discuss strategies, try solutions, and reflect on the results of activities. Therefore, active learning models can become an alternative for PJOK learning in vocational schools because they help students experience movement more meaningfully and participate more confidently.